2023
DOI: 10.3390/vaccines11050943
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pneumococcal, Influenza, and COVID-19 Vaccinations on COVID-19 Hospitalization and Progression in People over 65 Years Old Living in Nursing Homes

Abstract: Infectious diseases pose a major threat to elderly populations. Streptococcus pneumonia bacteria, influenza-causing viruses, and COVID-19 viruses cause three pathologies in the respiratory system with similar symptoms, transmission routes, and risk factors. Our study aimed to evaluate the effects of pneumococcal, influenza, and COVID-19 vaccinations on the status of COVID-19 hospitalization and progression in people over 65 years of age living in nursing homes. This study was performed in all nursing homes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The study by Yılmaz et al demonstrated that a regimen of four doses of the COVID-19 vaccine, in combination with the influenza and pneumococcal vaccines, offered protection among elderly individuals living in nursing homes [23]. In the study conducted by Liang et al, among the participants who received the influenza vaccine, 60.7% had received at least one dose of the COVID-19 vaccine [24].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Yılmaz et al demonstrated that a regimen of four doses of the COVID-19 vaccine, in combination with the influenza and pneumococcal vaccines, offered protection among elderly individuals living in nursing homes [23]. In the study conducted by Liang et al, among the participants who received the influenza vaccine, 60.7% had received at least one dose of the COVID-19 vaccine [24].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiology, morbidity, and mortality are also key concerns, with data provided on specific COVID-19 infection rates, outbreaks, and mortality. The effects of gender, chronic illness, and vaccination on COVID-19-related hospitalization and death are detailed, with male sex identified as a particular risk factor [ 29 , 30 ]. Importantly, the need to balance infection prevention with residents’ quality of life is a recurring theme, emphasizing the complexities of managing COVID-19 in these sensitive environments [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, vaccinations and their effects are a focal point, with evidence demonstrating that the availability of influenza and pneumococcal vaccines has a positive impact on COVID-19 progression in the elderly population living in nursing homes [28]. This notion is supported by consensus statements that promote extensive influenza and pneumococcal vaccination campaigns, even hinting at possible protection against COVID-19 [29]. Epidemiology, morbidity, and mortality are also key concerns, with data provided on specific COVID-19 infection rates, outbreaks, and mortality.…”
Section: Literature Findingsmentioning
confidence: 99%
“…In the context of the broader pandemic, our study time frame of July 2020-December 2021 reflects nursing home administrator discussions of COVID-19 outbreaks which occurred both pre-and post-vaccine. This distinction is noteworthy as the COVID-19 vaccine significantly reduced the morbidity and mortality of the virus for nursing home residents (Yilmaz et al, 2023;Barnett, 2023, McConeghy et al, 2022;Mor et al, 2021). Yet, even after the deployment of vaccines, administrators acknowledged experiencing overwhelming COVID-19 outbreaks (with fewer deaths) at their facilities once the Delta variant became dominant (Dykgraaf et al, 2021;LaFuente-LaFuente et al, 2022).…”
Section: Expanded Workloads To Accommodate Testing Infection Control ...mentioning
confidence: 99%